Damage Probability Matrices and Empirical Fragility Curves From Damage Data on Masonry Buildings After Sarpol-e-zahab and Bam Earthquakes of Iran - Biglari, Mahnoosh; Formisano, Antonio (Frontiers in Built Environment, 2020)
The weakness of tensile strength and high weight in masonry structures under the dynamic loads of earthquakes has always led to structural damage, financial losses, injuries, and deaths. In spite of cheap and affordable masonry materials, their use has been very limited in constructions over the past three decades. However, common masonry materials are still found in monumental and historical structures, deteriorated texture, and rural buildings. Identifying the seismic behavior and the probability of the structural damage is vital for pre-earthquake seismic risk reduction of urban areas and the rapid post-earthquake assessment. The earthquake event that occurred in Ezgeleh on 2017 November 12 with Mw = 7.3 triggered the greatest damage in Sarpol-e-zahab city at a distance of about 37 km from the epicenter. Post-earthquake reconnaissance, microtremor analysis, and rapid visual inventory of structural damages in different zones were performed by research teams. In the present study, the strong ground motion and the peak ground acceleration, and its corresponding intensity distribution, which are based on the site response analysis in different parts of the city, are introduced. Afterward, damage probability matrices of different types of masonry buildings, namely unreinforced masonry and confined masonry buildings, are determined for both bins of peak ground accelerations and intensities. Finally, the fragility curves of two types of masonry structures are extracted based on the RISK-UE level 1 (LM1) method by assuming a beta distribution to estimate the probability distribution function of the damage. These curves are useful in assessing pre-earthquake possible damages in masonry structures with similar construction methods and similar materials to reduce seismic risks.